2017
DOI: 10.1016/j.jsxm.2017.04.673
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sexual Difficulties and Sexual Counseling in Men and Women Across Heart Diagnoses: A Nationwide Cross-Sectional Study

Abstract: Background Ischemic heart disease and heart failure often lead to sexual difficulties in men, but little is known about the sexual difficulties in women and patients with other heart diagnoses or the level of information patients receive about the risk of sexual difficulties. Aim To investigate perceived sexual difficulties and associated factors in a mixed population of men and women newly diagnosed with heart disease and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Previous studies have shown that CVD patients have preferred to receive information about sexuality from health professionals (Abramsohn et al., ; Akhu‐Zaheya & Masadeh, ). However, patients have reported that they have not been informed regarding sexuality after a cardiovascular event (Rundblad et al., ). Clearly, there are major gaps in patients’ needs and nurses’ attitude about sexuality care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CVD patients have preferred to receive information about sexuality from health professionals (Abramsohn et al., ; Akhu‐Zaheya & Masadeh, ). However, patients have reported that they have not been informed regarding sexuality after a cardiovascular event (Rundblad et al., ). Clearly, there are major gaps in patients’ needs and nurses’ attitude about sexuality care.…”
Section: Discussionmentioning
confidence: 99%
“…We found men to have significantly greater knowledge on the subject than women. Several studies have concluded that women were significantly less informed and less likely to receive sexual counseling and that men had comparatively higher knowledge than women regarding the subject [17][18][19]. This is because, in a patriarchal society, sex is an easily spoken subject among men.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual concerns, which are disturbances in the sexual response cycle, are frequently reported in individuals diagnosed with coronary artery disease (CAD) (American Psychiatric Association 2013). Indeed, more than half of men and a quarter of women diagnosed with CAD report sexual concerns (Rundblad et al 2017). The deleterious impact of CAD on sexuality can also be illustrated by the fact that fewer individuals diagnosed with CAD report being sexually active compared to individuals without CAD (Steptoe et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual concerns have been linked to anxiety, depressive symptoms, and feelings of despair for individuals with CAD and their partners (Steinke et al 2013). Moreover, more than half of individuals with CAD report not feeling informed about their sexuality and see the resuming of sexual activities as challenging (Byrne et al 2014;Rundblad et al 2017). Importantly, individuals with CAD generally do not know that their sexual concerns may be caused, or exacerbated, by CAD.…”
Section: Introductionmentioning
confidence: 99%